Radiator Coolant Temperature Control System Based on Inlet-Outlet Temperature Difference Using Fuzzy Logic Controller - Bagus Tri Pambudi; Zakiyah Amalia (PT. ELSHAD TECHNOLOGY INDONESIA, 2026)
The radiator cooling system plays an important role in maintaining optimal engine operating temperature. To improve the effectiveness of coolant temperature control, it is necessary to select a control method that is able to provide a good system response. This study aims to compare the performance of ON/OFF control and Sugeno type Fuzzy Logic Controller (FLC) in the control system. Tests were conducted at ΔT setpoints of 2°C, 4°C, and 6°C. System performance was evaluated based on the parameters of rise time, overshoot, settling time, steady-state error (SSE), and mean absolute error (MAE). The test results showed that the Fuzzy method produced a rise time that was 8.28% faster, an average overshoot that was 8.15% lower, a settling time that was 6.48% faster, and a smaller MAE that was 11.33% lower than the ON/OFF method. Based on the evaluation of system response parameters, the Fuzzy method was considered more suitable for application in the ΔT-based radiator coolant temperature control system.